2022
DOI: 10.3389/fphys.2022.912277
|View full text |Cite
|
Sign up to set email alerts
|

The Allelic Variant A391T of Metal Ion Transporter ZIP8 (SLC39A8) Leads to Hypotension and Enhanced Insulin Resistance

Abstract: The metal ion transporter ZIP8 (SLC39A8) mediates cellular uptake of vital divalent metal ions. Genome-wide association studies (GWAS) showed that the single-nucleotide polymorphism (SNP) variant A391T (rs13107325) is associated with numerous human traits, including reduced arterial blood pressure, increased body mass index and hyperlipidemia. We analyzed in vitro the transport properties of mutant ZIP8 A391T and investigated in vivo in mice the physiological effects of this polymorphism. In vitro, the intrins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Less is known about lead uptake by these receptors, but it has been suggested that ZIP8 can transport lead, as lead reduces zinc uptake by the ZIP8 transporter [ 60 ]. Lastly, in mice with mutant ZIP8, cobalt levels in the kidney were reduced [ 61 ], suggesting a role for ZIP8 in cobalt reabsorption in the kidney.…”
Section: Handling Of Heavy Metals By the Kidneymentioning
confidence: 99%
“…Less is known about lead uptake by these receptors, but it has been suggested that ZIP8 can transport lead, as lead reduces zinc uptake by the ZIP8 transporter [ 60 ]. Lastly, in mice with mutant ZIP8, cobalt levels in the kidney were reduced [ 61 ], suggesting a role for ZIP8 in cobalt reabsorption in the kidney.…”
Section: Handling Of Heavy Metals By the Kidneymentioning
confidence: 99%
“…Findings in mice fed a high fat diet found that toll-like receptor 7 (TLR7) stimulation enhanced dysglycemia and hyperinsulinemia in mice ( Kakalij et al, 2022 ). Human genetic studies revealed a variant in a metal ion transporter ZIP8 (SLC39A8) that leads to enhanced insulin resistance ( Verouti et al, 2022 ). Kidney disease in obese rats treated with lisinopril was the focus of another study.…”
Section: Grand Challenge: the Epidemic Of Metabolic Diseasesmentioning
confidence: 99%